Uji Antibakteri Ekstrak Batang Bajakah Berduri (Caesalpinia sumatrana Roxb.) terhadap Salmonella typhi ATCC 19430 - Mufidah, Annisa Nabilah; Yeni, Laili Fitri; Wahyuni, Eko Sri (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
Thorny bajakah (Caesalpinia sumatrana Roxb.) is a plant from the Fabaceae family known to contain secondary metabolites with antimicrobial activities. This study aimed to examine the antibacterial activity and the effect of variation in the concentration of thorny bajakah stem extract against Salmonella typhi ATCC 19430. The samples included thorny bajakah stem extracts at concentrations of 12.5%, 25%, 50%, and 100%, along with a negative control (10% DMSO) and a positive control (0.001% chloramphenicol). Extraction was done using maceration with 96% ethanol as the solvent, while an antibacterial test was carried out using the disc diffusion method. Antibacterial tests showed the inhibition zones by each treatment of 12.5%, 25%, 50%, and 100% were 3.05 mm, 3.89mm, 3.69mm, and 4.56mm. The 100% concentration extract has the highest average diameter of the inhibition zone, even though it is considered very weak according to the Morales standard (<6mm). The antimicrobial activity is affected by the composition of secondary metabolites in the extract present as alkaloids and terpenoids, which are known to have antimicrobial activity. These results provide a basis for further research to develop the potential of thorny bajakah as a plant-derived antibacterial agent.